A Comprehensive Review of Slipping Rib Syndrome: Treatment and Management - Gress, Kyle (Psychopharmacol Bull, 2020)
PURPOSE OF REVIEW: This is a comprehensive review and update on advances in the understanding and treatment of slipping rib syndrome. It covers the physiology and pathophysiology at the basis of the syndrome, epidemiology and clinical presentation as well as diagnosis. It goes on to review the available literature to provide description and comparison of the available methods for alleviation. RECENT FINDINGS: Slipping rib syndrome stems from irritation of intercostal nerves. It is caused by slipping of the costal cartilage and the resulting displacement of a false rib and pinning underneath the adjacent superior rib and nerve irritation. It is rare and spans genders and ages; most evidence about epidemiology is conflicting and mostly anecdotal. Risk factors include trauma and high intensity athletic activity. Presentation is of a sudden onset of pain with jerking motion; the pain can be localized, radiating or diffuse visceral. It is often alleviated by positions that offload the impinged nerve. Diagnosis is clinical, and can be aided by Hooking maneuver and dynamic ultrasound. Definitive diagnosis is with pain relief on nerve block, visualization of altered anatomy during surgery and relief after surgical correction. Initial treatment includes rest, ice and NSAIDs, as well as screening for co-morbid conditions, as well as local symptomatic relief. Injection therapy with local anesthetics and steroids can provide a diagnosis as well as symptomatic relief. Surgical correction remains the definitive treatment. SUMMARY: Slipping rib syndrome is a rare cause of chest pain that could be perceived as local or diffuse pain. Diagnosis is initially clinical and can be confirmed with nerve blocks and surgical visualization. Initial treatment is symptomatic and anti-inflammatory, and definitive treatment remains surgical. More recently, advanced surgical options have paved way for cure for previously hard to treat patients.